Patient Safety In Hospitals : An Overview (VIMS Health Science Journal, 2014)
Ebola is one of the most lethal virus that infects primates. This virus first recognised in 1976, when two unrelated Ebola Haemorrhagic Fever (EHF) outbreaks occurred in Yambuku & Nzara. It was named as EBOLA after the small river near the catholic mission of Yambuku, the epicentre of 1976 EHF outbreak. It belongs to the family Filoviridae in the order Mononegaviriales. Transmission human to human or animal to human through contact with infected blood or bodily fluids or by contact with contaminated medical equipment’s. Bats are considered the most likely natural reservoir of the EBOV. Typical infection runs its course within 14-21 days. Infection initially present with non specific symptoms such as fever, myalgia, malaise, headache, joint & muscle pain, abdominal pain, vomiting, diarrhea and loss of appetite are common. As the infection progresses patient exhibits bleeding and coagulation abnormalities. Laboratory diagnosis detection of viral antigen by ELISA or RT-PCR are useful. There is no FDA approved antiviral treatment for EHF. Supportive management palliative care has to be practiced.
Keywords: Ebola; Ebola Haemorrhagic Fever; EHF